2021
DOI: 10.1016/j.jbior.2020.100760
|View full text |Cite
|
Sign up to set email alerts
|

The phosphoinositide 5-phosphatase INPP5K: From gene structure to in vivo functions

Abstract: INPP5K (Inositol Polyphosphate 5-Phosphatase K, or SKIP (for Skeletal muscle and Kidney enriched Inositol Phosphatase) is a member of the phosphoinositide 5-phosphatases family. Its protein structure is comprised of a N-terminal catalytic domain which hydrolyses both PtdIns(4,5)P2 and PtdIns(3,4,5)P3, followed by a SKICH domain at the C-terminus which is responsible for protein-protein interactions and subcellular localization of INPP5K. Strikingly, INPP5K is mostly concentrated in the endoplasmic reticulum, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Members include Lowe oculocerebrorenal syndrome protein (OCRL), inositol polyphosphate 5-phosphatase B (INPP5B), SH2-containing inositol 5-phosphatase1/2 (SHIP1/2), synaptojanin1/2 (SYNJ1/2), inositol polyphosphate 5-phosphatase E (INPP5E), proline rich inositol polyphosphate 5-phosphatase (INPP5J) and inositol polyphosphate 5-phosphatase K (INPP5K) [1] . INPP5K can use two lipid substrates PI(4,5)P 2 and PI(3,4,5)P 3 to generate PI4P and PI(3,4)P 2 , respectively [2] . The human INPP5K is a 448 amino acid protein with an N-terminal catalytic domain and a INPP5K carboxy homology C-terminal domain responsible for protein-protein interactions as well as subcellular distribution of the phosphatase [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members include Lowe oculocerebrorenal syndrome protein (OCRL), inositol polyphosphate 5-phosphatase B (INPP5B), SH2-containing inositol 5-phosphatase1/2 (SHIP1/2), synaptojanin1/2 (SYNJ1/2), inositol polyphosphate 5-phosphatase E (INPP5E), proline rich inositol polyphosphate 5-phosphatase (INPP5J) and inositol polyphosphate 5-phosphatase K (INPP5K) [1] . INPP5K can use two lipid substrates PI(4,5)P 2 and PI(3,4,5)P 3 to generate PI4P and PI(3,4)P 2 , respectively [2] . The human INPP5K is a 448 amino acid protein with an N-terminal catalytic domain and a INPP5K carboxy homology C-terminal domain responsible for protein-protein interactions as well as subcellular distribution of the phosphatase [2] .…”
Section: Introductionmentioning
confidence: 99%
“…INPP5K can use two lipid substrates PI(4,5)P 2 and PI(3,4,5)P 3 to generate PI4P and PI(3,4)P 2 , respectively [2] . The human INPP5K is a 448 amino acid protein with an N-terminal catalytic domain and a INPP5K carboxy homology C-terminal domain responsible for protein-protein interactions as well as subcellular distribution of the phosphatase [2] . Most recent studies have concluded PI(4,5)P 2 to be the preferred substrate of the phosphatase [3] , [4] , [5] , [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%